Perception and satisfaction of parents and speech therapists with performance on auditory skills and language children with cochlear implants (Research, Society and Development, 2021)
To analyze and discuss comparatively the perception of parents and audiologists - therapists and programmers, for the hearing and language skills in children with cochlear implants, process satisfaction and the factors responsible for it.  The subjects of this research 50 children under fifteen years of age, cochlear implant users, who underwent surgery at least six months of the first ear. With this, their parents and audiologists were also subject of this research.  Ace language categories compared to parents and respondents and non-respondents therapists there was a statistically significant association (p = 0.143). In both groups the majority of children are category 5 language, but in children of non-respondents parents observed a higher number of children in categories 1, 2 and 3. Since the hearing categories, there was also no statistically significant association (p = 0.099) between parents and respondents and non-respondents therapists, however there is a greater number of children in the categories 1, 2, 3 and 4 of the non-respondents parents. The vast majority of study participants demonstrated satisfied with the performance of children. The results seem to indicate that the clinical markers - language categories and hearing has the potential to strengthen the partnership between parents and audiologists (therapists and developers) and we can highlight the common factors of parents and speech therapists related to meeting the communicative performance, audibility / IC, academic performance and involvement of the parties involved.